2016
DOI: 10.5152/iao.2016.2086
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness of the 7-item Eustachian Tube Dysfunction Questionnaire

Abstract: OBJECTIVE:Baro-challenge-induced Eustachian tube (ET) dysfunction is defined as the presence of aural discomfort, popping, or pain, which only arises in case of ambient pressure changes, without abnormalities on otoscopy or tympanometry. Our primary aim was to determine the discriminative power of the 7-item Eustachian Tube Dysfunction Questionnaire (ETDQ-7) in patients with baro-challenge-induced ET dysfunction in comparison with that in healthy controls. The secondary aim was to determine the responsiveness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
1
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 5 publications
1
38
1
5
Order By: Relevance
“…Duration of symptoms, timing of worsening symptoms with associated diseases such as rhinosinusitis or reflux should be assessed with the medical history. Roeyen et al [17] assessed patients with baro-challengeinduced ETD and healthy controls using the ETDQ-7. The authors reported that ETQD-7 was useful in the diagnosis of baro-challengeinduced ETD dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Duration of symptoms, timing of worsening symptoms with associated diseases such as rhinosinusitis or reflux should be assessed with the medical history. Roeyen et al [17] assessed patients with baro-challengeinduced ETD and healthy controls using the ETDQ-7. The authors reported that ETQD-7 was useful in the diagnosis of baro-challengeinduced ETD dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…History and subjective symptoms with a quantifying instrument (Eustachian Tube Dysfunction Questionnaire [ETDQ]-7) 29 was not intended for diagnosis and it has been misused for that purpose. 30 Weakness of the ETDQ-7 in differentiating different types of ETD was pointed out in recent publications. 31,32 Any questionnaire based on patient symptoms is expected to have limited reliability in children, especially when parents are the responders.…”
Section: Discussionmentioning
confidence: 99%
“…However, development of solutions and their use for treatment preceded the development of a clear definition and testing criteria for ETD. History and subjective symptoms with a quantifying instrument (Eustachian Tube Dysfunction Questionnaire [ETDQ]‐7) was not intended for diagnosis and it has been misused for that purpose . Weakness of the ETDQ‐7 in differentiating different types of ETD was pointed out in recent publications .…”
Section: Discussionmentioning
confidence: 99%
“…In der Literatur wird der Erfolg der Tubendilatation in der Mehrzahl mit > 70 % angegeben [6,7,9]. Die Erfolgsparameter sind jedoch nicht einheitlich und reichen von der subjektiven Einschätzung der Patientenzufriedenheit über die Durchführbarkeit des SVT-Tests, die Auswertung von Tympanogrammen [10] und Messung anhand unterschiedlicher Tubenscores bis hin zur Evaluation anhand von Fragebögen wie des "Eustachian Tube Dysfunction Questionaire" (ETDQ7) [11,12]. Hinzu kommt, dass die Größe der untersuchten Patientenkollektive einer erheblichen Schwankungsbreite unterliegt.…”
Section: Diskussionunclassified